Three-dimensional imaging of the plasma parameters of a moving cusp aurora. (October 2015) - Taguchi, Satoshi; Hosokawa, Keisuke; Ogawa, Yasunobu
Abstract: During a period of negative IMF BZ on 13 January 2013, an all-sky imager at Longyearbyen, Svalbard observed a mesoscale aurora moving towards the east-northeast in the cusp, passing through the field of view of the EISCAT Svalbard Radar (ESR) elevation scan. The elevation scans that were being performed at that time have a horizontal coverage of approximately 300 km, at an altitude of 300 km. The plasma data obtained from the elevation scans and the 630-nm aurora emission data from the all-sky imager have shown that ion temperature enhanced 50–60 s earlier than electron density, and that the maximum auroral intensity in the ESR's field of view occurred about 40 s after the electron density enhancement. On the basis of these results we have constructed three-dimensional images of elevated ion temperatures and enhanced electron density associated with the mesoscale moving cusp aurora. The three-dimensional image shows that the enhancement of the ion temperature is prominent in the horizontal area of ~160 km×~80 km below an altitude of ~300 km, and that this volume forms on the forward side of the enhanced electron density region. We interpret these configurations as being a result of a mesoscale twin-cell convection, which is embedded in the background flow such that the symmetrical axis of the twin-cell is inclined from the background flow direction by several tens of degrees. Our method for visualizing three-dimensional features such as these could be an effective approach to understanding the mesoscale dynamics of the cusp, which is usually located in latitudes that are difficult for the currently-operated radars that permit three-dimensional, simultaneous measurements to investigate. Highlights: 3D images of plasma parameters in a moving aurora from IS radar and all-sky imager. Spatial relations are found between the cusp aurora, elevated Ti, and enhanced Ne. The relationships are explained by the presence of a moving twin-convection cell.